Hubungan Lama Menderita Diabetes Melitus Dengan Kejadian Hipertensi Pada Pasien Dm Tipe Ii Di RSUD Dr.Sadikin Kota Pariaman - Asfri Sri Rahmadeni; Yani Selvia (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2023)
Diabetes Mellitus is a result of disorders of the pancreas that does not produce enough insulin. The purpose of this study was to determine the relationship between the duration of suffering from DM with the incidence of hypertension in type II DM patients. The type of research used is correlational analytics with a Cross sectional approach. The number of samples in this study was 52 respondents using the Prposive sampling technique. The respondents taken were aged > 45 years with a long suffering from DM > 5 years. The results showed a relationship between the length of suffering from DM with the incidence of hypertension in type II DM patients with results (p Value = 0.004). Respondents must always routinely control blood sugar levels and blood pressure in order to maintain their health, and nurses need to take measurements of the length of suffering from DM with the incidence of hypertension to type II DM patients to prevent more severe DM complications.